High-absorption high-emission composite functional film coating material and preparation method thereof

By using fluorine-containing resin, zirconia, carbon black and other materials to prepare high-absorbing and high-emission composite functional films, the problem of poor high-temperature curing adaptation during the spraying and curing of satellite surfaces is solved, and efficient thermal management and solar light absorption and infrared emission functions are achieved.

CN119775687AActive Publication Date: 2025-04-08SHANGHAI INST OF SATELLITE EQUIP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411890888.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-08
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The existing ultra-black coating materials have poor high-temperature curing adaptation during the spraying and curing of satellite surfaces, resulting in the problem of degradation of material performance and long implementation cycle.

Method used

High absorption and high emission composite functional films are prepared using fluorine-containing resins, zirconia, carbon black and other materials, and integrated on the satellite surface through scraping or spraying.

Benefits of technology

The high absorption and high emission composite functional film is prepared, with excellent thermal control performance and vacuum deflation performance, and can maintain stable performance within the temperature range of -100~+100℃, reducing the detectability of satellites in orbit and compatible with thermal control requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775687A_ABST
    Figure CN119775687A_ABST
Patent Text Reader

Abstract

The invention discloses a high-absorption and high-emission composite functional thin film coating material and a preparation method thereof, and relates to the technical field of flexible thin film material preparation, a carbon material, inorganic ceramic particles and other multi-scale materials are used as main functional units, organic fluorine-containing resin is used as a binder, precursor slurry is prepared in an organic solvent, and the precursor slurry is subjected to high-absorption and high-emission composite functional thin film coating material is prepared. The composite functional thin film is prepared through blade coating, spraying and other processes, the process is simple, the prepared thin film is a thin film ultra-black material with the flexible characteristic and can be integrated with the satellite surface through double faced adhesive tape, hidden buckle lap joint and other modes, the implementation period of the high-absorption and high-emission composite functional material can be greatly shortened, and the application range is wide. And meanwhile, the problem of poor high-temperature curing adaptability of a spraying curing type ultra-black coating material is also solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of flexible film material preparation, and in particular to a high-absorption and high-emission composite functional film coating material and a preparation method thereof. Background Art

[0002] With the continuous development of international space optical surveillance systems, the safety and survivability of satellites in orbit are facing increasingly severe threats. Therefore, research on reducing satellite sunlight detection technology in orbit has become a trend in satellite safety research. There are many ways to reduce satellite sunlight, among which spraying ultra-black coating materials on the surface of satellites is a simple and effective way.

[0003] Ultra-black material is a material with a reflectivity of less than 5% and an absorptivity of more than 95% for incident light within a certain range. Since satellites are subject to thermal control design restrictions when working in orbit, ultra-black materials are required to have a high infrared emissivity, thereby achieving a composite functional ultra-black material that reduces the detectability of sunlight and is compatible with thermal functions. This coating is widely used in many fields such as optical equipment and aerospace. For example, in the internal structure of a space telescope, the use of ultra-black coating can reduce stray light reflection and improve the imaging quality of the optical system.

[0004] From the perspective of thermal management, when the ultra-black coating absorbs a large amount of visible light and electromagnetic radiation in other bands, this energy is converted into heat. If the heat cannot be effectively dissipated, the temperature of the coating and the object to which it is attached will continue to rise. This may lead to a decrease in coating performance, such as material aging, deformation and other problems, and may also affect the accuracy of some high-precision equipment. Ultra-black coatings are mainly integrated on the surface of satellites through processes such as spraying and high-temperature curing. However, with the continuous shortening of satellite development cycles, the gradual improvement of development efficiency, and the poor high-temperature adaptability of some materials, spray-cured ultra-black coating materials have obvious limitations. Summary of the invention

[0005] In view of this, an object of the present invention is to provide a method for preparing a high-absorption and high-emission composite functional film.

[0006] The objective of the present invention is achieved through the following technical solutions:

[0007] <First aspect>

[0008] The present invention provides a composite functional film, comprising a fluorine-containing resin, a first filler and a second filler, wherein the mass ratio of the three is (0.75-6):1:(2-5); the fluorine-containing resin is one or more of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, and polyvinylidene fluoride-chlorotrifluoroethylene; the first filler is one or more of zirconium oxide, silicon dioxide, and hafnium boride; the second filler is one or more of high-pigment carbon black, carbon aerogel, and carbon spheres.

[0009] As an embodiment, the thickness of the composite functional film is 50-100 μm.

[0010] <Second Aspect>

[0011] The present invention provides a method for preparing a high-absorption and high-emission composite functional film, comprising the following steps:

[0012] S1, dissolving the fluorine-containing resin in an organic solvent, then adding a first filler and a second filler, and mixing them evenly through stirring to obtain a precursor slurry;

[0013] S2. Applying the precursor slurry on the surface of the substrate by scraping or spraying, and obtaining the composite functional film after drying.

[0014] As an embodiment, the fluorine-containing resin is one or more of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, and polyvinylidene fluoride-chlorotrifluoroethylene.

[0015] As an embodiment, the first filler is one or more of zirconium oxide, silicon dioxide, and hafnium boride.

[0016] In some embodiments, the first filler is one of monoclinic zirconium oxide, amorphous silicon dioxide, and amorphous hafnium boride.

[0017] As an embodiment, the particle size of the first filler is no more than 20 μm.

[0018] In some embodiments, the first filler has a particle size of no greater than 10 μm.

[0019] As an embodiment, the second filler is one or more of high-pigment carbon black, carbon aerogel, and carbon spheres.

[0020] As an embodiment, the particle size of the second filler is nanometer scale.

[0021] As an embodiment, the organic solvent is one or more of N,N-dimethylformamide, N,N-dimethylacetamide, and butyl acetate.

[0022] In some embodiments, the organic solvent is N,N-dimethylacetamide or butyl acetate.

[0023] As an embodiment, the mass ratio of the first filler to the second filler is 1:(2-5).

[0024] As an embodiment, the mass ratio of the fluorine-containing resin to the filler is 1:(1-4), and the filler is a first filler and a second filler.

[0025] As an embodiment, in step S1, the stirring treatment parameter is 300-600 r / min.

[0026] As an embodiment, in step S1, the stirring treatment time is 1 to 4 hours.

[0027] As an embodiment, in step S2, the substrate is a glass substrate.

[0028] As an embodiment, in step S2, the drying temperature is 50-100°C.

[0029] As an embodiment, in step S2, the drying time is 6 to 12 hours.

[0030] As an embodiment, the thickness of the prepared composite functional film is 50-100 μm.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] 1) The present invention provides a method for preparing a high-absorption and high-emission composite functional film, which uses multi-scale materials such as carbon materials and inorganic ceramic particles as main functional units, and an organic fluorine-containing resin as a binder. A precursor slurry is prepared in an organic solvent, and the composite functional film is prepared by scraping, spraying and other process methods. The process is simple, and the prepared film is a thin-film ultra-black material with flexible characteristics, which can be integrated with the satellite surface by double-sided tape, concealed buckle overlap and other methods, which can greatly reduce the implementation cycle of the high-absorption and high-emission composite functional material, and also solves the problem of poor high-temperature curing adaptability of spray-cured ultra-black coating materials.

[0033] 2) The high-absorption and high-emission composite functional film prepared by the present invention has a thickness of 50 to 100 μm, excellent thermal control performance (solar absorption ratio and hemispherical emissivity), excellent vacuum degassing performance, and after undergoing 100 temperature shock tests in the temperature range of -100 to +100°C, not only has an intact appearance and stable performance, but is also a composite functional film with high absorption of sunlight and high emission of infrared.

[0034] 3) From the perspective of thermal management, after absorbing solar radiation, the composite functional film prepared by the present invention dissipates heat into space with the help of enhanced infrared emission capability, ensuring that the surface temperature of the satellite is maintained in an appropriate range, which not only ensures the normal operation of the precision instruments and equipment inside the satellite, but also maintains the stability of the overall structure of the satellite. Furthermore, since the satellite reflects very little sunlight when facing solar radiation, the possibility of being discovered by sunlight detection equipment is greatly reduced.

[0035] In summary, the high-absorption and high-emission composite functional film provided by the present invention has the excellent performance of reducing the detectability of sunlight during satellite in-orbit operation and being compatible with thermal control requirements, solving the problems of poor compatibility between satellite solar high-absorption materials and thermal control, long production cycle, and poor high-temperature curing adaptability. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0037] Figure 1 A flow chart of the method for preparing the high-absorption and high-emission composite functional film provided by the present invention;

[0038] Figure 2 The solar light absorption characteristic curve of the composite functional film prepared in Example 4 of the present invention;

[0039] Figure 3 Before the high and low temperature test of the composite functional film prepared in Example 4 of the present invention ( Figure 3 (a)) and after the test ( Figure 3 (b)) Sample image. DETAILED DESCRIPTION

[0040] The present invention is described in detail below in conjunction with embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, some adjustments and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0041] This specific embodiment provides a method for preparing a high-absorption and high-emission composite functional film, such as Figure 1 As shown, the following steps are included:

[0042] S1. Preparation of precursor slurry

[0043] Dissolving the fluorine-containing resin in an organic solvent, then adding a first filler and a second filler, and stirring the slurry to mix the slurry evenly to obtain a precursor slurry;

[0044] S2. Forming and preparing composite functional film

[0045] The precursor slurry is coated on the surface of the substrate by scraping or spraying, and a high-absorption and high-emission composite functional film with a thickness of 50 to 100 μm is obtained after drying.

[0046] The following four embodiments are used to specifically introduce the method for preparing the high-absorption and high-emission composite functional film.

[0047] Example 1

[0048] In this embodiment, the substances and their amounts are as follows:

[0049] Fluorine-containing resin: 3 parts of polyvinylidene fluoride (PVDF);

[0050] First filler: 1 part high pigment carbon black;

[0051] Second filler: 2 parts of monoclinic zirconium oxide with a particle size of 0.5 to 1 μm;

[0052] Organic solvent: 3 parts of N,N-dimethylacetamide.

[0053] In this embodiment, a scraping coating method is adopted to coat the thin film on the surface of the glass substrate.

[0054] In step S1, the stirring parameters are: rotation speed 300 r / min, stirring time 1 h.

[0055] In step S2, the drying temperature is 100°C and the drying time is 12 hours.

[0056] A 55 μm thick high-absorption and high-emission composite functional film was prepared.

[0057] Example 2

[0058] In this embodiment, the substances and their amounts are as follows:

[0059] Fluorine-containing resin: 2 parts of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP);

[0060] First filler: 1 part carbon aerogel;

[0061] Second filler: 3 parts of 5-8 μm amorphous silicon dioxide;

[0062] Organic solvent: 3 parts of N,N-dimethylacetamide.

[0063] In this embodiment, a scraping coating method is adopted to coat the thin film on the surface of the glass substrate.

[0064] In step S1, the stirring parameters are: rotation speed 400 r / min, stirring time 2 h.

[0065] In step S2, the drying temperature is 80°C and the drying time is 10 hours.

[0066] A 73 μm thick high-absorption and high-emission composite functional film was prepared.

[0067] Example 3

[0068] In this embodiment, the substances and their amounts are as follows:

[0069] Fluorine-containing resin: 5 parts of polyvinylidene fluoride-chlorotrifluoroethylene (P(VDF-CTFE));

[0070] First filler: 3 parts of hollow nano carbon spheres with a size of 100-300 nm;

[0071] Second filler: 12 parts of 1-3 μm amorphous hafnium boride;

[0072] Organic solvent: 10 parts of butyl acetate.

[0073] In this embodiment, a scraping coating method is adopted to coat the thin film on the surface of the glass substrate.

[0074] In step S1, the stirring parameters are: rotation speed 500r / min, stirring time 3h.

[0075] In step S2, the drying temperature is 50°C and the drying time is 6 hours.

[0076] A 96 μm thick high-absorption and high-emission composite functional film was prepared.

[0077] Example 4

[0078] In this embodiment, the substances and their amounts are as follows:

[0079] Fluorine-containing resin: 3 parts of polyvinylidene fluoride-hexafluoropropylene;

[0080] First filler: 2 parts carbon aerogel;

[0081] Second filler: 10 parts of 5-8 μm silicon dioxide;

[0082] Organic solvent: 7.5 parts of N,N-dimethylacetamide.

[0083] In this embodiment, a scraping coating method is adopted to coat the thin film on the surface of the glass substrate.

[0084] In step S1, the stirring parameters are: rotation speed 600r / min, stirring time 4h.

[0085] In step S2, the drying temperature is 60°C and the drying time is 8 hours.

[0086] A high-absorption and high-emission composite functional film with a thickness of 87 μm was prepared.

[0087] Test Method

[0088] (I) Coating thickness test

[0089] The thickness of the composite functional film was tested using an external micrometer produced by Chengdu Chengliang Tool Group Co., Ltd. The measuring range was 0-25 mm, with an error of ±5 μm. The thickness of the composite functional film tested was between 55 and 96 μm (as described in each embodiment), meeting the technical indicator requirement of 50 μm-100 μm.

[0090] (II) Solar absorption ratio test

[0091] This experiment uses the LAMBDA950 spectrophotometer produced by Perkin Elmer to measure the solar absorption ratio of the composite functional film. It can measure the wavelength range from 200nm to 2500nm, the resolution of the instrument is 0.1nm, the bandwidth is ≤0.05nm, the stray light is ≤0.00008%A, the noise is <0.0008A, the photometer repeatability is <0.0001A, the baseline drift is <0.0002A / h, the baseline is straight: ±0.001A, the stability is good, the baseline is high in straightness, and the stray light is extremely low. In the experiment, the step size is set to 5nm and the slit width is set to 4nm.

[0092] (III) Hemispherical emissivity test

[0093] The hemispherical emissivity of the sample in the 3-35 μm band at room temperature was measured using the TEMP 2000A emissivity meter developed by AZ TECHNOLOGY. Its measurement accuracy is ±3% and the full-band repeatability is ±0.5%.

[0094] (IV) Vacuum degassing performance test

[0095] The vacuum degassing test was carried out in accordance with the standard GJB2704A-2006 to test and calculate the total mass loss (TML) and condensable volatile matter (CVCM) of the material in vacuum. The test conditions are as follows:

[0096] Sample pre-treatment: 23℃±1℃, humidity 45%RH±10%RH, maintain for 24h; sample heating temperature 125℃±1℃; condensable volatile collection temperature 25℃; test pressure ≤7×10 -3 Pa; insulation time is 24h;

[0097] Balance test sensitivity: lμg.

[0098] (V) Thermal Cycle Test

[0099] A temperature shock chamber (model ZTS010, Shanghai Zengda Environmental Testing Equipment Co., Ltd.) was used. According to the requirements of GJB2704A-2006 standard, 100 thermal cycles were performed at a temperature of -100°C to +100°C under normal atmospheric conditions. The test conditions are as follows:

[0100] Test temperature: high temperature end temperature is 100℃, low temperature end temperature is set to -100℃; cycle 100 times; temperature control error: high temperature ±5℃, low temperature ±10℃; the thermal cycler should have two constant temperature areas with different temperatures, and the sample is transferred from one constant temperature area to another within 10s; keep warm at the high and low temperature ends for 10min to ensure that the sample temperature is the same as the ambient temperature; dehumidification measures should be taken during the test to prevent frost on the surface of the test piece.

[0101] Test results and analysis

[0102] The performance of the composite functional films prepared in the above examples 1, 2, 3 and 4 was tested, and the test results are listed in Table 1. The solar light absorption characteristic curve of Example 4 and the sample pictures before and after the high and low temperature test are shown in Table 1. Figure 2 and Figure 3 shown.

[0103] Table 1 Performance test data of the composite functional films prepared in each embodiment

[0104]

[0105]

[0106] As shown in Table 1, the properties of the composite functional film prepared by the present invention are as follows:

[0107] Appearance: black, uniform coating surface;

[0108] Thickness: 50μm-100μm;

[0109] Solar absorption ratio: 0.95~0.98;

[0110] Hemispherical emissivity: 0.88-0.93;

[0111] Thermal cycle test: After the high-absorption and high-emission composite functional film meets the high and low temperature thermal cycle test of -100~+100℃ for 100 times, the appearance is intact and the optical performance is stable;

[0112] Vacuum degassing performance: both meet TML<1%, CVCM<0.1%.

[0113] It can be seen that the high-absorption and high-emission composite functional film prepared by the present invention has the advantages of reducing the detectability of sunlight when the satellite is in orbit and being compatible with thermal control performance (solar absorption ratio, hemispherical emissivity). It has the advantages of simple preparation process and short integration period with the satellite surface. It has strong feasibility and has intact appearance and stable performance after undergoing 100 temperature shock tests in the temperature range of -100 to +100°C.

[0114] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A composite functional film, characterized in that: It includes a fluorine-containing resin, a first filler and a second filler, and the mass ratio of the three is (0.75-6):1:(2-5); the fluorine-containing resin is one or more of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, and polyvinylidene fluoride-chlorotrifluoroethylene; the first filler is one or more of zirconium oxide, silicon dioxide, and hafnium boride; the second filler is one or more of high-color carbon black, carbon aerogel, and carbon balls.

2. The composite functional film according to claim 1, characterized in that: The thickness of the film is 50-100 μm.

3. The method for preparing a composite functional film according to any one of claims 1 to 2, characterized in that: The following steps are involved: S1, dissolving the fluorine-containing resin in an organic solvent, then adding a first filler and a second filler, and mixing them evenly through stirring to obtain a precursor slurry; S2, coating the precursor slurry on the surface of the substrate, and obtaining the composite functional film after drying.

4. The method for preparing the composite functional film according to claim 3, characterized in that: The mass ratio of the fluorine-containing resin to the filler is 1:(1-4), and the filler is a first filler and a second filler.

5. The method for preparing the composite functional film according to claim 3, characterized in that: The organic solvent is one or more of N,N-dimethylformamide, N,N-dimethylacetamide and butyl acetate.

6. The method for preparing the composite functional film according to claim 3, characterized in that: The particle size of the first filler is no more than 20 μm.

7. The method for preparing the composite functional film according to claim 3, characterized in that: The particle size of the second filler is nanometer scale.

8. The method for preparing the composite functional film according to claim 3, characterized in that: The stirring process has a speed of 300 to 600 r / min and a time of 1 to 4 hours.

9. The method for preparing a composite functional film according to claim 3, characterized in that: The drying temperature is 50-100°C.

10. The method for preparing a composite functional film according to claim 3, characterized in that: In step S2, the substrate is a glass substrate.

Citation Information

Patent Citations

  • Core-shell-type ultra black powder material and preparation method thereof

    CN110952075A

  • Inorganic ultra-black thermal control coating with high absorption, high incidence and low condensable volatile matter content and preparation method of inorganic ultra-black thermal control coating

    CN116855106A

  • High-emission thermal control film and preparation method thereof

    CN118421028A

  • High-emissivity coating composition and production process thereof

    JP2018184615A

  • Composite conductors including radiative and / or hard coatings and methods of manufacture thereof

    US20230307155A1